Karakteristik Kualitas Tidur pada Siswa SMA Negeri 1 Sukawati, Gianyar - I Putu Palguna Ananta Kesuma; Putu Asih Primatanti; I Gusti Rai Tirta (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2023)
Sleep quality disturbances are quite common in high school students. This is due to them being in the late period of puberty that is causing changes in their sleep patterns. In general, sleeping quality of high school students can be influenced by various factors which can be divided into two, intrinsic factors that are based on the person themselves, and extrinsic factors that are based on that person’s surroundings or environment. This study employs a descriptive research design. The participants in this study consist of the students from SMA Negeri 1 Sukawati. The utilized tools encompass the PSQI and PSS-10 questionnaires. The sampling method employed is simple random sampling with a total of 735 respondents.. Data processing was carried out using SPSS with univariate and bivariate analysis. 59.5% of high school students were found to have poor sleeping quality by using univariate analysis. Using bivariate analysis using chi square, it was discovered that there are several characteristics that are related to sleep quality (P<0.05) namely gender, family situation, and number of close friends. In addition, stress levels were also found to have a significant connection with sleep quality (P <0.05). Based on the findings of this study, it can be inferred that a majority of students at SMA Negeri 1 Sukawati experience sleep disturbances, amounting to 59.5%. The variables, including gender, family environment, number of acquaintances, and stress levels, have demonstrated a statistically significant correlation with sleep quality, with a p-value of <0.05.